Short Note: First report of Cryptosporidium spp. oocysts in stool of Adélie penguin from the Antarctic using acid-fast stain - Fredes, Fernando; Raffo, Eduardo; Muñoz, Pamela (Antarctic Science, 2007)
Cryptosporidium is an intracellular parasite that belongs to the phylum Protozoa and subphylum Apicomplexa (Sporozoa). It was first described by from the digestive tract of laboratory mice (Garcia 2001), and has been found in several animal groups including fishes, reptiles, birds and mammals, including humans (Jellison et al . 2002).